Avaliação dos efeitos de vento em linhas de transmissão - Hermes Carvalho (2015)
In transmission lines, the main load to be considered in the structural analyses is produced by wind, which acts dynamically in the system (towers, cables and insulator strings). Considering that several accidents involving towers of this type occurred, although the wind speed used in the project has not been reached, the collapse might have been caused by dynamic actions or some mistake in the wind effect estimate. Bearing such motivation in mind, this study aims to evaluate the tower transmission requests due to wind effect on the structural system. The static behavior of the structural assembly has already been evaluated, in masters dissertation, evaluated using a three-dimensional model comprising tower, cables and insulator chains, with the performance of equivalent static wind loads and consideration of geometric non-linear effects. For the dynamic behavior, a space model of an isolated cable is evaluated, considering the geometric non-linear effects and the aerodynamic damping, with a huge influence in cases in which the structure assumes speed next to the wind speed. The wind loading is modeled as a random process from statistical properties. For future applications, an experimental data collection program was developed and installed in a suspension tower in operation of 138 kV transmission line, owned by the Energetic Company of Minas Gerais (CEMIG). In this tower a three-dimensional anemometer responsible for measuring values and direction of wind speeds was installed. Simultaneously measured deformation values of the main elements of the tower can be evaluated by means of optical extensometers, using Fiber Bragg Grating technology. These extensometers feature immunity to stronger electromagnetic field values due to electric currents. The chain balance angle can be evaluated through a high-resolution camera and a three-dimensional accelerometer, both located along the insulators. With the instrumentation used it becomes possible to create a database associating the wind speeds with answers from the structural assembly (cables, chains of insulators and transmission tower).